The Effect of Product Quality and Price on Purchase Decisions: A Quantitative Study of University Students Using the Shopee E-Commerce Platform - Neng Riny Rahmawati; Deni Rohmat (JOURNAL EKONOMI, KEUANGAN, PERBANKAN DAN AKUNTANSI SYARIAH, 2025)
: The rapid growth of e-commerce in Indonesia has positioned Shopee as the most visited platform among university students, yet empirical research specifically examining how product quality and price jointly influence purchase decisions within this digital-native consumer segment remains limited. This study aims to analyse the partial and simultaneous effects of product quality and price on purchase decisions among students of STIE STAN Indonesia Mandiri who use Shopee. A quantitative explanatory design was employed, with data collected through a structured questionnaire administered to 86 respondents drawn from a population of 610 students using purposive sampling. The instrument measured three constructs product quality (8 items), price (5 items), and purchase decision (11 items) on a five-point Likert scale. Data was analysed using descriptive statistics, classical assumption tests, Pearson correlation, multiple linear regression, the F-test, and the t-test in SPSS version 25. Descriptive results indicate that respondents' assessments of all three constructs fall within the high category. Inferential analysis confirms that product quality (β = 0.293, t = 2.824, p = 0.006) and price (β = 0.517, t = 4.979, p < 0.001) each exert a positive and significant partial effect on purchase decisions, with price emerging as the stronger predictor. Simultaneously, both variables explain 57.3% of purchase-decision variance (R² = 0.573, F = 55.709, p < 0.001). The findings extend the marketing-mix literature for the Indonesian e-commerce context and offer practical guidance for Shopee sellers targeting price-sensitive student consumers